2022
DOI: 10.1002/ggn2.202100055
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Analysis of Extracellular Vesicle‐Mediated Metastasis Using a Bright, Red‐Shifted Bioluminescent Reporter Protein

Abstract: Cancer cells produce heterogeneous extracellular vesicles (EVs) as mediators of intercellular communication. This study focuses on a novel method to image EV subtypes and their biodistribution in vivo. A red-shifted bioluminescence resonance energy transfer (BRET) EV reporter is developed, called PalmReNL, which allows for highly sensitive EV tracking in vitro and in vivo. PalmReNL enables the authors to study the common surface molecules across EV subtypes that determine EV organotropism and their functional … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 78 publications
2
13
0
Order By: Relevance
“…We have previously utilized PalmReNL [ 30 ] as a dual-reporter for bioluminescence and fluorescence tracking of EVs in vitro and in vivo. In the current study, we generated HEK293FT cells stably expressing PalmReNL and selected the EV donor cells that maintained a high level of PalmReNL expression ( Figure 1 A,B).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously utilized PalmReNL [ 30 ] as a dual-reporter for bioluminescence and fluorescence tracking of EVs in vitro and in vivo. In the current study, we generated HEK293FT cells stably expressing PalmReNL and selected the EV donor cells that maintained a high level of PalmReNL expression ( Figure 1 A,B).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, PalmReNL can be used as a fluorescent EV reporter for standard microscopy and flow cytometry as well. We previously demonstrated that the labeling efficiency of PalmReNL was 1.2% for small EVs as determined by flow cytometry [ 30 ]. However, individual EVs carry probe molecules not detectable by flow cytometry due to the background autofluorescence.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations